Diversity and Distribution of Phytoplankton at selected sites of Jamnagar coast, Gujarat, India - Bhagat, Roshan; Patel, Rajal; Salvi, Harshad; R.D., Kamboj (International Journal of Scientific Research in Biological Sciences, 2019)
Phytoplanktons are the primary producer of marine ecosystems and contribute towards the primary productivity of aquatic environment. The present study was carried out at three selected sites of Gulf of Kachchh (GoK) viz; Pirotan, Sachana and Roziport. During the study, a total of 106 species of phytoplankton were recorded, of which the highest species diversity was found at Rozi followed by Pirotan and Sachana. The maximum number of species diversity was contributed by the class Bacillariophyceae with 81.5 percentage , 79 percentage and 83 percentage at Pirotan, Rozi and Sachana, respectively. Rozi port reported the highest number of harmful phytoplankton i.e. some members of Bacillariophyceae and Dinophyceae. The highest number of species was recorded at Rozi port (75 sp.) followed by Pirotan (54 sp.) and Sachana (46 sp.). The varied environmental conditions prevailing at three study sites may cause variation in species composition at these sites